Socioeconomic and Cultural Determinants of Early Marriage in Ngawi, East Java: Application of PRECEDE-PROCEED Model - Noviana Ayumi Wijayati; RB. Soemanto; Ety Poncorini Pamungkasari (Journal of Health Promotion and Behavior, 2017)
Background: Indonesia ranks 37 of the countries in the world with the highest rate of early marriage. Center for Gender and Sexuality Studies, University of Indonesia reported in 2015 that Indonesia rank the second highest rate of early marriage in South East Asia. Approximately 2 millions (7.3%) girls aged under 15  years old have been married and dropped out of school. This number is expected to become 3 million married girls in 2030. This study aimed to determine the effect of socioeconomic and cultural factors on early marriage in Ngawi, East Java.Subjects and Method: This was an analytical observational study with case control design. Study subjects consisted of 75 women of reproductive age who got married before 20 years old and 75 women of reproductive age who got married had 20-30 years of age. The dependent variable was early marriage. The independent variables were paternal education level, maternal education level, family income, family belief, culture, and peers. The data were collected by a set of questionnaire and analyzed by path analysis model.Results: Early marriage was positively affected by family belief (b=1.47; 95% CI= 0.44 to 2.50; p=0.005) and culture (b=1.56; 95% CI= 0.54 to 2.58; p=0.003). Early marriage was negatively affected by family income (b=-2.20; 95% CI= -3.18 to -1.21; p<0.001) and positive peers (b=-2.51; 95% CI= -3.58 to -1.44; p<0.001). Family income was affected by paternal education (b=2.24; 95% CI= 0.37 to 4.12; p=0.019) and maternal education (b= 6.53; 95% CI= 4.25 to 8.80; p<0.001). Family belief  was affected by paternal education (b= -1.20; 95% CI= -2.10 to -0.30; p= 0.009) and maternal education (b= -1.20; 95% CI= -2.10 to -0.30; p= 0.009).Conclusion: Early marriage is directly affected by family income, family belief, culture, and positive peers.Keyword: early marriage, family education, family income, family belief, culture, peersCorrespondence: Noviana Ayumi Wijayati. Masters Program in Public Heath, Sebelas Maret University, Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java. Email: novianaayumi@gmail.com. Mobile: +6285645828766.Journal of Health Promotion and Behaviour (2017), 2(4): 302-312https://doi.org/10.26911/thejhpb.2016.02.04.02